SENTIMENT ANALYSIS UNTUK REVIEW DESTINASI WISATA UNGGULAN GUNUNG KIDUL MENGGUNAKAN METODE LEXICON DAN PIVOT - Larasati Larasati; Shalsa Nabilla; Eri Haryanto (Universitas Alma Ata, 2022)
Sentiment analysis is the process of using text analytics to get various data sources from the internet and various social media platforms. Comment data is obtained through Twitter social media. This classification is used to determine how comments interpret tourist attractions in Gunungkidul. Lexicon-based and Pivoting are used to group people's opinions into three classes: positive, negative, and neutral sentiments. This method is used to classify the results of community comment data written as community satisfaction with tourism in Gunungkidul. This study aims to discover people's opinions about tourism in Gunungkidul during the Covid-19 pandemic. The results of this study are used to determine the classification of community comment data so that services can be easily developed through comments provided by the community. The sentiment analysis results contained the categories of positive emotions 51%, negative 1%, and neutral 48%.